2010
DOI: 10.1148/radiol.10091982
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Intracranial Unruptured Aneurysms: Systematic Review and Meta-Analysis of the Literature on Safety and Efficacy

Abstract: EVT of UAs can be performed with relative safety. The efficacy of treatment as compared with observation has not been rigorously documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
149
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(159 citation statements)
references
References 78 publications
6
149
0
4
Order By: Relevance
“…3,4 In our series, most complications were evident during the procedure or on awakening from anesthesia.…”
Section: Discussionmentioning
confidence: 68%
“…3,4 In our series, most complications were evident during the procedure or on awakening from anesthesia.…”
Section: Discussionmentioning
confidence: 68%
“…3,6,16,17 In SENAT, the morbidity and mortality in the periprocedural period at 1 month (0% and 0%) and at 12-18 months (1% and 1%), were low and were comparable to the major coiling series of UIA in the literature. A recent meta-analysis published by Naggara et al 36 showed a morbidity rate of 4.8% and a mortality rate of 1.2%. In the International Study of Unruptured Intracranial Aneurysm, 37 the morbidity rate was 9.1% and the mortality rate was 2%.…”
Section: Discussionmentioning
confidence: 96%
“…The results of coiling in the published studies are better than those of clipping, with most articles and meta-analysis data suggesting morbidity rates of approximately 5%, 5 in line with these articles suggesting approximately 5% discharge rate to continuing care facilities or rehabilitation. Caution should be exercised in directly comparing the clipping and coiling data from these studies.…”
mentioning
confidence: 56%